Perceptions of formal organizational processes of graduate schools in four teacher education institutions - Sebastian, Lourdes (Molina) (1971)
This study investigates how the student and faculty respondents in four teacher education institutions perceive the formal organizational processes of their graduate schools. It also evaluates the extent to which student and faculty perceptions differ from each other.
Thesis (D.Ed.)--University of the Philippines, Diliman.
Keywords: Education -- Graduate work; Graduate students -- Philippines